2021
DOI: 10.1016/j.apnu.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The experience of frontline nurses four months after COVID-19 rescue task in China: A qualitative study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
2
24
0
Order By: Relevance
“…In other words, the higher the pride of nurses, the better they play the role assigned to them within the organization, and have a positive effect on improving the quality of nursing care services [18]. These results are the same as a study [28] that reported that 15 nurses in charge of rescue work for COVID-19 patients in tertiary hospitals experienced increased professional pride and a study [17] that reported that 'I felt proud of my job as a nurse' in interviewing 43 nurses' experiences.…”
Section: Discussionsupporting
confidence: 60%
“…In other words, the higher the pride of nurses, the better they play the role assigned to them within the organization, and have a positive effect on improving the quality of nursing care services [18]. These results are the same as a study [28] that reported that 15 nurses in charge of rescue work for COVID-19 patients in tertiary hospitals experienced increased professional pride and a study [17] that reported that 'I felt proud of my job as a nurse' in interviewing 43 nurses' experiences.…”
Section: Discussionsupporting
confidence: 60%
“…Geriatric nurses working in nursing homes in four countries (Spain, Italy, Peru, and Mexico) reported on their professional pride and perceived satisfaction from the happiness and gratitude felt by the nursing home residents and their families (Sarabia‐Cobo et al, 2021 ). Nurses in China also expressed a sense of professional pride and happiness in being on the front line to fight COVID‐19 by providing patient care and saving patients (Zhang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Later on these negative emotions sometimes led to post-traumatic stress disorder [30,31] or burnout [32,33]. The psychological picture naturally varied over time; a few months after the acute phase of the epidemic, both recurring involuntary memories and happiness were described [34]. The type of occupational problems to which workers were exposed changed over the course of the pandemic: in the early stages, lack of readiness, a shortage of PPE, separation from families, stigma [35], and an increased workload [36,37] prevailed among professionals, whereas in later stages, other stressors such as the death of patients and colleagues inducing moral injury and distress [38,39], isolation or lack of support at work [40,41] attracted the attention of researchers.…”
Section: Discussionmentioning
confidence: 99%